Exploring EFL Students’ Perceptions of Using Padlet in Collaborative Academic Writing - Novitaningrum, Angella; Yuswandari, Kurnia Devi; Daristin, Pipit Ertika (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
This study investigates how students perceive the use of Padlet in collaborative academic writing. As digital platforms become increasingly integrated into language classrooms, understanding learners’ engagement with these technologies is essential for optimizing pedagogical outcomes. It employed a descriptive qualitative research design that involved 14 third-semester undergraduate students from the English Education Study Program at STIT Miftahul Midad Lumajang as the participants. The data of this study were collected through semi-structured interviews, classroom observations and documentation. The findings reveal five major themes that reflect students’ perceptions in using Padlet for collaborative academic writing, including enhanced engagement and confidence, support for the writing process, technological and interpersonal challenges, emotional and cognitive impact and metacognitive reflective practice. These themes provide a comprehensive understanding of how Padlet mediates students’ engagement, interaction, and learning development in digitally supported writing context. Overall, the study highlights Padlet’s potential to transform academic writing from an individual task into a dynamic, socially situated learning experience that promotes engagement, reflection, and collaborative knowledge construction in digital EFL contexts.